Rydberg Energy Levels and Quantum Defects of some Semiconductor Elements - Ejaz Ahmed; Jehan Akbar (Journal of Basic & Applied Sciences, 2018)
Weakest bound Electron Potential Model Theory has turned out to be a successful theory in explaining many atomic properties, namely, energy levels, transition probabilities and oscillator strengths. The theory has also been used to calculate Rydberg energy levels and quantum defects. In this paper we studied semiconductor elements Boron and Silicon. We calculated energy levels of Rydberg atoms of Boron and Silicon up to n = 50 levels using WBEPMT. We also calculated quantum defects in principle quantum number for various configurations of these elements.